High Performance Sodium Ion Anodes Based on Sn4P3 Encapsulated within Amphiphilic Graphene Tubes. Issue 2 (10th December 2021) - Tan, Xinyi; Mo, Runwei; Xu, Jinhui; Li, Xinru; Yin, Qingyang; Shen, Li; Lu, Yunfeng
Abstract: High‐performance sodium‐ion anode composites are synthesized through confined growth Sn4 P3 nanoparticles within amphiphilic graphene tubes, which provide mechanical robustness, the ability to confine Sn4 P3 particles with their highly conductive frameworks, and the capability to accommodate the volume change of the particles during cycling. This unique structure endows a sodium‐ion anode with high reversible capacity (821 mA h g −1 ), excellent rate capability (326 mA h g −1 at 20 A g −1 ), and cycling stability (>90% reversible capacity retention after 500 cycles). This strategy can be extended to other conversion‐ and alloying‐type materials that experience dramatic volume change during charging and discharging. Abstract : A high performance sodium ion anode is prepared by encapsulating Sn4 P3 within amphiphilic and porous graphene tubes (GT). The amphiphilic GTs consist of an inner hydrophilic graphene tube and an outer hydrophobic graphene tube, which guarantee confined growth of Sn4 P3 nanoparticles within the GT and effective accommodation of the volume expansion of nanoparticles.